PERTENTANGAN KELAS DALAM JEJAK TANAH: KAJIAN SASTRA MARXIS ATAS EKSPLOITASI KAUM PROLETAR KARYA DANARTO - Mu'amar, Afadi Khoirul; Mustika, Gina; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to analyze class conflict and forms of proletarian exploitation in the short story Jejak Tanah by Danarto through the lens of Marxist theory. The story portrays a structural conflict between property developers, representing the bourgeois class, and the marginalized community as the proletariat struggling to defend their land rights. This research employs a qualitative method with a critical literary text analysis approach to uncover intrinsic and extrinsic elements in the story that reflect social, political, and economic dynamics. The analysis reveals that Jejak Tanah voices a critique of modern capitalist practices, particularly in the form of land grabbing, structural violence, and repression of popular resistance. The story also contains symbolic narratives that reflect class consciousness and the collective struggle of the proletariat against bourgeois domination. Thus, Danarto’s work not only aesthetically represents social injustice but also calls on readers to recognize the importance of solidarity in resisting oppression.